Fertility preservation services and COVID-19: the urgent need for phase two. Issue 5 (2020) - Daolio, Jessica; Nicoli, Alessia; Panfilis, Ludovica De; Morini, Daria; Feo, Gaetano De; Falbo, Angela; Aguzzoli, Lorenzo; Villani, Maria Teresa
No abstract available